Rhetorical Devices in the Presidential Speeches of the President of the Republic of Indonesia in the Reformation Era - ., Noermanzah (KnE Social Sciences, 2018)
This study applied the method of critical discourse analysis (CDA) using the model of Norman Fairclough. The data collection techniques used in this study were documentation, libraries, interviews, and notes. The data analysis techniques were connecting elements micro, mediate, and macro elements in three dimensions: (1) text, (2) discourse practice, and (3) social practice culture. The results showed that the rhetorical devices used were as follows: 1) the most dominant diction used was denotation, popular, scientific; 2) the most dominant sentence used was a release sentence; 3) the most dominant cohesion used was classical anaphora cohesion, repetition, conjunction of cause, effect, conflict, way, purpose, condition, and time; and (4) the most dominant coherence was the coherence of cause, effect, conflict, purpose, manner, condition, and time. The presidential speech was structured into the following stages: invention, disposition, elocution, memorial, and pronunciation in manuscript and memoriter. The rhetorical tools used described the educational programs already undertaken, the promises, and the hope of improving the quality of education in Indonesia. Keywords: presidential speech, reformation era, rhetorical device